1995
DOI: 10.1007/bf00206836
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy in the elderly

Abstract: An evaluation of the utility, morbidity, and patient tolerance of colonoscopy in elderly (> or = 70 years) patients was undertaken and compared to data for a similar group of younger patients (50-70 years) who underwent colonoscopy during the same 48 months. Data reviewed for both groups included demographics, indications for colonoscopy, effectiveness of bowel preparation, colonoscopy completion, endoscopic findings, and complications. The mean age of the entire 656-patient population was 69 +/- 10 years; 87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 11 publications
1
43
0
8
Order By: Relevance
“…Several reports on the findings of colonoscopy among older individuals support these findings. 16,28 The results of this study showed that 32.3% of the young had colorectal polyps detected by total colonoscopy, and 53.3% of the older patients had colorectal polyps detected (χ 2 test, p<0.001). However, the proportion of adenomas among the colorectal polyps in the young patients was comparable to the older patients as shown in Table 4 (64.0% vs 68.9%, p=0.310).…”
Section: Discussionmentioning
confidence: 73%
“…Several reports on the findings of colonoscopy among older individuals support these findings. 16,28 The results of this study showed that 32.3% of the young had colorectal polyps detected by total colonoscopy, and 53.3% of the older patients had colorectal polyps detected (χ 2 test, p<0.001). However, the proportion of adenomas among the colorectal polyps in the young patients was comparable to the older patients as shown in Table 4 (64.0% vs 68.9%, p=0.310).…”
Section: Discussionmentioning
confidence: 73%
“…Bat et al [10] , 1992 436 80+ 63% 14% 29.80% Ure et al [48] , 1995 354 70+ 78% 6% 24% Sardinha et al [49] , 1999 403 80+ 94% 4.50% -Clarke et al [12] , 2001…”
Section: Completion Cancers Adenomas/ Polypsmentioning
confidence: 99%
“…Az 50 év feletti aszimptómás betegcsoportokban végzett screening kolonoszkópiák kevesebb mint 1%-ában fordul elő vastagbélrák [38,39]. Jelentősen magasabb gyakoriságokat (3,3%-7,1%) kö-zölnek olyan tanulmányok, amelyekben szimptómás, fennjáró, illetve kórházi bennfekvő betegek egyaránt szerepelnek [35,40,41]. Az általunk megfigyelt 6,9%-os előfordulási gyakoriság igen magasnak tekinthető, azonban megfelel más, hasonlóan idős, polimorbid betegeket nem kizáró betegpopulációjú vizsgálatok adatainak [40,41].…”
Section: Megbeszélésunclassified